2017
DOI: 10.4172/2315-7844.1000226
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Effective Leadership Style in Successful Merger and Acquisition Growth Strategy of Ecobank Ghana

Abstract: The study examined how effective leadership style assisted in motivation employees of Ecobank Ghana towards the successful implementation of its merger and acquisition growth strategy. In conducting the study, purposive sampling technique was adopted to select key officials of the bank, key managers and supervisors of the bank whose leadership styles influenced employees to work hard towards turning the new consolidated bank around. Out of 120 questionnaires distributed, 104 returned safely which enabled the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Implementing business transformation redistributes the interests among the subjects of an enterprise, causing much strife and internal struggle and leading to resistance against the business transformation. Overconfident managers usually have a vigorous and resolute style and dare to overcome difficulties (Asamoah, 2017). They firmly believe that their decisions are correct.…”
Section: Managerial Cognitive Bias and Business Transformation Performancementioning
confidence: 99%
“…Implementing business transformation redistributes the interests among the subjects of an enterprise, causing much strife and internal struggle and leading to resistance against the business transformation. Overconfident managers usually have a vigorous and resolute style and dare to overcome difficulties (Asamoah, 2017). They firmly believe that their decisions are correct.…”
Section: Managerial Cognitive Bias and Business Transformation Performancementioning
confidence: 99%
“…Tummers and Knies () observed that public leaders support their followers fully in public sector organizations. Other research by Asamoah () explored how an effective leader style affected bank mergers in Ghana. Asamoah found that effective leadership style had an effect on the merger and the acquisition, and it ensured a smooth implementation.…”
Section: Introductionmentioning
confidence: 99%